FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN (Study Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada tahun 2014-2016) - Ina Dwi Indrayani, 13.05.52.0224; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
This study aims to analyze the influence of institutional ownership, independent commissioner, external auditor, firm size, and leverage to integrity of financial statement. The population of this study is companies registered in Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2016 . The sampling technique using purposive sampling and mchanical testing data is to use a multipe linear regression analysis.The analysis showed that the variables institutional ownership, independent commissioner and firm size had no effect on integrity of financial statement. External auditor and leverage had effect on integrity of financial statement.Keywords: Institutional Ownership, Independent Commissioners, External Auditors, Firm Size, Leverage, Integrity of Financial Statements